2006
DOI: 10.1002/elps.200500661
|View full text |Cite
|
Sign up to set email alerts
|

Less common applications of monoliths: I. Microscale protein mapping with proteolytic enzymes immobilized on monolithic supports

Abstract: This review summarizes the recent contributions to the rapidly growing area of immobilized enzymes employing both silica and synthetic polymer-based monoliths as supports. Focus is mainly on immobilized proteolytic enzyme reactors designed for studies in proteomics. Porous monoliths emerged first as a new class of stationary phases for HPLC in the early 1990s. Soon thereafter, they were also used as supports for immobilization of proteins and preparation of both stationary phases for bioaffinity chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 92 publications
0
95
0
Order By: Relevance
“…With the unique properties of simplicity of preparation, rapid mass-transfer rate, low backpressure, and versatile surface modification, monolithic materials have been more and more attractive and widely used in proteomic analysis [21,22]. Since Malik et al [23] first prepared a C 18 -incorprated hybrid monolith, the organic-silica hybrid monolith has drawn more attentions in the separation field [24,25], which combines the advantages of both organic monolith and inorganic monolith, such as easily fabricated, less shrinkage and good pH stability.…”
Section: Introductionmentioning
confidence: 99%
“…With the unique properties of simplicity of preparation, rapid mass-transfer rate, low backpressure, and versatile surface modification, monolithic materials have been more and more attractive and widely used in proteomic analysis [21,22]. Since Malik et al [23] first prepared a C 18 -incorprated hybrid monolith, the organic-silica hybrid monolith has drawn more attentions in the separation field [24,25], which combines the advantages of both organic monolith and inorganic monolith, such as easily fabricated, less shrinkage and good pH stability.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the sample volume is only 40 µ L per analysis. Moreover, no trypsin autolysis peaks were observed from mass spectra in the microwave-assisted digestion method, which demonstrated that enzyme immobilization technique can overcome the trypsin autolysis (Dogruel et al, 1995;Nelson, 1997;Gobom et al, 1997; Jiang et al, 2000; Ekstrom et al, 2000;Peterson et al, 2002;Licklider et al, 1995;Ma et al, 2007;Svec, 2006). Since the magnetic microspheres are excellent microwave absorbers; and thus greatly improve the efficiency of protein digestion.…”
Section: Microwave-assisted Protein Enzymatic Digestionmentioning
confidence: 98%
“…In both approaches, to obtain detailed structural information, proteins are selectively cleaved into smaller polypeptide fragments by controlled chemical or enzymatic reactions Wolters et al, 2001;Zhu et al, 2003 (Nalivaeva and Turner, 2001). The immobilized enzyme has been adopted to characterize the proteins with benefits from the reusability and stability of enzyme, the higher digestion efficiency of protein analytes, and no enzyme autolysis products (Dogruel et al, 1995;Nelson, 1997;Gobom et al, 1997; Jiang et al, 2000; Ekstrom et al, 2000;Peterson et al, 2002;Licklider et al, 1995;Ma et al, 2007;Svec, 2006). The main approach of enzyme immobilization is covalent binding.…”
Section: Abstract: Mesoporous Sio 2 Microspheres ; Peptide Mapping Anmentioning
confidence: 99%
“…Their applications in a variety of liquid chromatographic modes including high-performance liquid chromatography (HPLC) and capillary electrochromatography (CEC) has recently been described in several reviews [12][13][14][15][16][17][18][19][20][21][22][23][24][25] and books [11,26]. However, the less common applications of monolithic materials that include supports for solid phase and combinatorial synthesis [27][28][29], scavengers [30,31], carriers for immobilization of enzymes [32][33][34], static mixers [35], thermally responsive gates and valves [36][37][38], as well as solid phase extractors and pre-concentrators [39] are escaping the awareness of the scientific community. The recently started series of review articles aims at popularization of these applications.…”
Section: Introductionmentioning
confidence: 99%
“…The recently started series of review articles aims at popularization of these applications. So far, this series detailed achievements in microscale protein mapping with proteolytic enzymes immobilized on monolithic supports and in preconcentration and solid-phase extraction [34,39]. Present contribution focuses on use of monolithic materials in gas chromatography.…”
Section: Introductionmentioning
confidence: 99%